Sensitivity of bean and corn Rhizoctonia species to chemical fungicides - Rabago-Zavala, Karen; Valenzuela-Escoboza, Fernando Alberto; López-Valenzuela, Blanca Elvira; Ayala-Armenta, Quintín Armando; Pérez-Mora, Juan Luis (Revista Mexicana de Ciencias Agrícolas, 2025)
In the northern region of Sinaloa, the fungus Rhizoctonia spp. causes plants to dry and rot in beans and corn, affecting germination, growth, and roots. This weakens and causes death in plants. Farmers often seek to mitigate the disease by applying chemical fungicides; however, the effectiveness of these treatments is often limited. This is due to inappropriate selection of fungicides, incorrect dosing during application, and pathogens’ potential acquired resistance to these compounds, among other factors. The purpose of this study was to evaluate the in vitro sensitivity of Rhizoctonia isolates from beans and corn to four synthetic fungicides (Azoxystrobin, Benomyl, Methyl thiophanate and Tebuconazole). A completely randomized design was performed, using the commercial dose of each fungicide and a control, with three replications per treatment. The conventional fungicide tebuconazole proved to be the most effective against all Rhizoctonia species evaluated, inhibiting growth by 100%. Effectiveness tests on the sensitivity of Rhizoctonia isolates to fungicides allow us to know the variability of behavior and facilitate the monitoring of isolates that present resistance to fungicides in the pathogen population. This is essential for the development of effective control strategies for Rhizoctoniasis.
Keywords: fungicides; resistance; rhizoctoniasis; tebuconazole